Relationship Between Riparian Buffers and Terrestrial Wildlife in the Eastern United States - Larsen-Gray, Angela L; Loehle, Craig (Journal of forestry, 2022)
Abstract When working forest stands are harvested, vegetated strips along streams are often retained as part of forestry best management practices (BMPs) to protect water quality. These riparian buffers, known as streamside management zones, when following forestry BMP recommendations, also likely provide benefits to various terrestrial wildlife species. To better understand the role of riparian buffers in contributing to biological diversity in working forest landscapes, we reviewed literature (n = 30) that reported on herpetofauna, bird, and mammal responses to riparian buffers in the eastern United States. Although few results were consistent among taxa, community composition commonly varied among riparian buffer widths. Narrower riparian buffers more commonly supported edge and disturbance-associated species whereas wider riparian buffers tended to support interior-associated species. We did not find a consistent width that supported all terrestrial wildlife species studied.